Design of an inventory control system for a toy store - Bermúdez del Sol, Abdel (2022)
The objective of this article was to design an inventory control system for a toy store in Puyo, Ecuador. Between November 2018 and February 2019, we characterized the actual situation of inventory management in the company in the first stage of the research; in the second stage, we designed the inventory system. For the analysis and design of the inventory management system of the toy store we combined two procedures, one unrelated to the characterization of the existing inventory system and the other related to inventory planning. We identified that the merchandise in the store was not codified and that the store lacked a storage system for its merchandise. We discovered that the stock available could not be identified. In addition, we determined the inventory parameters as a basis for the design of the automated system. An adequate inventory management will guarantee a timely supply of sales products and the minimization of the total cost of logistics activities in inventory control, ensuring better profitability and customer service.